Menganalisis kearifan tempatan dalam membentuk etika kepimpinan: Kajian terpilih Raja Ali Haji - Briando, Bobby (2024)
Leadership ethics is an important and frequently discussed topic, especially in the context of government management. In Indonesia, the quality of leadership in government agencies is still unsatisfactory, contributing to the poor level of service in the public service sector. Raja Ali Haji is one of the well-known local scholar who has been focusing on efforts to improve leadership ethics. The leadership ethics based on Raja Ali Haji’s selected works include: (1) Faith; (2) Ethical; (3) Knowing religion; (4) Believing; (5) Hereafter-oriented; (6) Being fair; (7) Being sincere; (8) Being knowledgeable; (9) Polite manners; (10) Being careful; (11) Serving; (12) Prioritizing deliberation; (13) Holding the trust; (14) Being charitable; (15) Being honest; (16) Being patient; (17) Being responsible; (18) Speaking and behaving softly; (19) Being humble; and (20) Loving kindness. This ethics index is consistent with the spiritual leadership theory proposed by Fry (2003) which consists of vision, altruistic love, and faith or hope. The analysis revealed a new concept which the reviewer refers to as the spiritual leadership ethics of Raja Ali Haji. This new ethic concept is more comprehensive than the one proposed by Fry because it is based on "Adat Bersendi Syara', Syara' bersendi Kitabullah". Through this philosophy, one attains a sense of calling and membership by recognising that the paramount aim is to prioritise all the teachings and commands of Allah SWT as the primary ethical guidance, and to follow the leadership traits of Prophet Muhammad SAW, namely “Siddiq, Amanah, Fathonah and Tabligh”. As a result, a leaders’ essential well-being, particularly the spiritual well-being will be enhanced, enabling them to lead and engage with their subordinate through ethical leadership.